A new love–hate scale for sports fans - Shuv-Ami, A.; Toder Alon, A.; Loureiro, S. M. C.; Kaufmann, H. R. (International Journal of Sports Marketing and Sponsorship, 2020)
Purpose: This study, an empirical research, aims to construct and validate a new love-hate scale for sports fans and tested its antecedents and consequences. Design/methodology/approach: The scale was designed and validated in three separate empirical survey studies in the context of Israeli professional basketball. In Phase 1, the authors verified the factorial validity of the proposed scale using exploratory factor analysis. In Phase 2, the authors conducted a confirmatory factor analysis using structural equation modeling. In Phase 3, the authors tested the nomological network validity of the scale. Findings: The findings show that fans' involvement, loyalty and fandom significantly predicted their love–hate, which in turn significantly predicted self-reported fan aggression, fans' acceptance of fan aggression, price premium and frequency of watching games. Research limitations/implications: The model was tested on a relatively small sample of fans within a single country. This lack of generalizability should be addressed in future studies by examining the model in other sports contexts and countries. Practical implications: This study suggests that understanding the properties of the love–hate measure may assist team sports clubs in identifying, preventing and controlling potential fan aggression. Originality/value: The study provides three incremental contributions above and beyond existing research: it develops and validates a scale for measuring the phenomenon of sports fans' love and hate as mixed emotions; it makes it possible to capture the variations in the magnitude of fans' love–hate; and it relates fans' love–hate to important attitudinal and behavioral outcomes.